Purwarupa Pengoperasian TV Dengan Mendeteksi Isyarat Jari Berbasis Pengolahan Citra Digital - Handreas Okta Wibawa; Agus Harjoko (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2015)
The development computer technology and electronics very rapidly at this time makes people start looking for other solutions to perform activities easier and more practical. Technologies are developed and can be used at this time it is possible to facilitate the activities human beings to operate TV with finger gesture.            In this research, digital image processing of technology can be used to operate TV using webcam and computer as image processing. Input this research is hand image that catched by webcam on computer. Then hand image processed through image processing system to obtain results form value fingers. This value indicates the number equal to number fingers detected by webcam camera on monitor screen. Microcontroller function is receives serial data from results image processing and serves serial data conversion value into instructions can operate TV. Color model used in research is HSV.                First step testing this research is setting room in order to capture image for get best results in any room. Results of the research found best value for testing operation TV with finger gesture is : for value light intensity is 12 lux, best distance is 70 cm and best baskground is blue.